Criteria to identify and define territories with productive development potential to establish Special Economic Zones of Development (SEZD) in Costa Rica - Arias Ramírez, Rafael (2015)
This study is aimed to identify, based on a series of variables and indicators, territories that have characteristics to propitiate an endogenous development, from the basis of the resource endowment they have, along with a productive policy, at the national and local level to promote it. A county´s index of productive potential is built around three components (productive, infrastructure and institutions); then a cluster analysis is applied. The outcomes of the study are not only new for the country, also they make a contribution with the elaboration of a matrix of variables and indicators, which provide criteria, empirically validated, to identify and define Special Economic Zones of Development (SEZD) for Costa Rica.